An updated checklist of fish species in the Sultan Idris Shah Forestry Education Centre, Puchong, Selangor, with notes on the occurrence of invasive species - Saba, Abdulwakil Olawale; Ismail, Muhammad Darwish Nazhan; Abdull Jamil, Muhammad Fadhlil Hakimi; Steward, Frasier Hoo Anak; Abdullah Halim, Muhammad Rasul; Ilham-Norhakim, Mohd Lokman; Zulkiply, Mohammad Amirul Faiz; Kamaruddin, Kamarulizwan; Shariff, Fazli; Amal, Mohammad Noor Azmai (Universiti Putra Malaysia Press, 2025)
This study presents an updated fish checklist of the Sultan Idris Shah Forestry Education Centre (SISFEC), Puchong, Selangor, Malaysia. Fish samples were collected using gill nets, cast nets, scoop nets, baited lines, and electrofishers at eight sites within SISFEC, including Rasau River, Bohol River, and several lentic water bodies. There are 29 fish species, representing 13 families of freshwater fish, with the family Danionidae (six species) dominating the list. Of the 29 species recorded, six were non-native, including Oreochromis niloticus, Barbonymus gonionotus, Puntigrus tetrazona, Pterygoplichthys disjunctivus, Oreochromis sp. (red), and Poecilia reticulata. In addition to the non-native species recorded, the Australian red claw crayfish, a non-native invasive invertebrate, was also encountered. Despite the increase in recorded native species compared to past reports, potential threats from invasive species remain a concern. Regular monitoring and strict regulation are recommended to ensure the conservation and sustainable use of SISFEC’s aquatic biodiversity.